2014
DOI: 10.11124/jbisrir-2014-1666
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Mindful Parenting programs in promoting parents' and children's wellbeing: a systematic review protocol

Abstract: Review question/objective The primary objective of this review is to systematically evaluate the effectiveness of Mindful Parenting programs in promoting children's, adolescents' and parents' wellbeing, particularly in relation to the intensity of symptoms associated with internalizing (depression, anxiety, stress) and externalizing (conduct) disorders. The secondary objective is to evaluate how effective Mindful Parenting programs are in improving emotional regulation, quality of the parent-child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…Parenting stress has been noted in other situations including in parents of children with paediatric cancer 44. Interventions including cognitive-behavioural therapy or mindful parenting45 may help parents with methods of coping and reduce their distress 44 46 47…”
Section: Discussionmentioning
confidence: 99%
“…Parenting stress has been noted in other situations including in parents of children with paediatric cancer 44. Interventions including cognitive-behavioural therapy or mindful parenting45 may help parents with methods of coping and reduce their distress 44 46 47…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based interventions like Mindfulness or Acceptance Commitment Therapy, for example, might be helpful for parents and caregivers of children with ASD. A systematic review suggests that mindfulness parenting interventions may reduce stress although more research is needed (Townshend et al, 2016). Intervention studies that alter narratives about the diagnosis, such as through expressive writing, may also promote better acceptance (Lovell, Moss, & Wetherell, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A MP training specifically aims to help parents cope with, and regulate their parental stress (Bögels et al 2010;Potharst et al 2018b). A systematic review and a recent meta-analysis provided insight in the effectiveness of a MP training and mindfulness interventions for parents of children of different ages and different settings (mental health setting and preventive setting), and showed reduced parental stress and improved child behavioral outcomes (Burgdorf et al 2019;Townshend et al 2016). In addition, a recent study on a MP training specifically designed for mothers with a toddler found improvements in parental stress, mother-toddler interactions, and toddler behavioral problems (Potharst et al 2018b).…”
mentioning
confidence: 99%